تصمیم الخدمات المعلوماتیة وفقا لاحتیاجات المستفیدین من مکتبات کلیات جامعة طنطا : دراسة تخطیطیة (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aimed to adopt analytical and planning frameworks for the implementation of future information services based on the needs of current and potential users from the libraries of Tanta University. This is based on the analytical descriptive approach, with the adoption of a method of content analysis to collect and analyze data and to help plan a comprehensive framework for the development of library services at Tanta University. The questionnaire was used as a data collection tool, which was distributed to a sample of faculty members and students of the faculties of Tanta University to survey their views on their needs for information services and to identify their future vision. And survey of a sample of international universities libraries that Design User Centered Services, to identify these services. The study concluded that the libraries of international universities have distinguished in services such as scientific publishing and Internet services and supporting information literacy, Users of libraries in Tanta University need to activate the role of the college libraries through the provision of internet services and other Electronic services. The study provided planning for the design of these services and others according to the needs of users. The study also concluded that costs, the need to qualify human in libraries, limited library space, and lack of technology are the most important challenges that may face the faculties of the University of Tanta libraries when adopting this approach.